(untitled) (Jurnal Pendidikan Fisika, 2026)
This study addresses the urgent need for interactive and contextual digital learning media that can foster higher-order thinking skills in physics, especially in culturally rich regions such as Ngada Regency, Indonesia. The study aimed to develop and evaluate a Nearpod-based digital teaching module incorporating Sui Wu’u Ngada local wisdom to improve senior high school students’ analytical thinking skills in thermodynamics. Using a research and development (R&D) approach with the ADDIE model (analysis, design, development, implementation, and evaluation), the module was designed with interactive features (e.g., quizzes, drag-and-drop tasks, videos, and local case-based activities) and culturally grounded contexts derived from Sui Wu’u practices. The module was implemented through guided learning with 32 grade XI students at Citra Bakti High School, supported by physics teachers. Data were analyzed using descriptive qualitative and quantitative methods, including expert validation, student response questionnaires, and pretest–posttest assessments of analytical thinking skills. The results showed that the developed module received a “very valid” rating, with an expert mean score of 4.72, and demonstrated “very practical” usability based on student responses (88%), indicating it was engaging, easy to use, and culturally relevant. Effectiveness testing indicated a significant improvement in analytical thinking skills, with an N-gain value of 0.67 (medium–high category). The novelty of this study lies in systematically integrating the specific local wisdom of Sui Wu’u Ngada into an interactive Nearpod digital module for thermodynamics learning, which remains rarely documented in regional physics education contexts. In conclusion, the Nearpod-based Sui Wu’u module is feasible, practical, and effective for improving students’ analytical thinking and contributes to physics education by providing an empirically supported model for culturally responsive, technology-enhanced learning in secondary education schools.